Diabetes ofthe Exocrine PancreasRelatedtoHereditary Pancreatitis, an Update - Ramalho, Gabriel Xavier (UniCEUB, 2020)
DEP due to HP appears to be a misdiagnosed condition. The requirement of specific management demonstrates the importance of this matter; therefore, appropriate recognition and classification are important.
Keywords: Hereditarypancreatitis; Diabetesoftheexocrinepancreas; Brittlediabetes; PRSS1; SPINK1